Completing the heterotrimer: Isolation and characterization of an Arabidopsis thaliana G protein γ-subunit cDNA - Mason, Michael G. (The National Academy of Sciences, 2000)
Heterotrimeric G proteins consist of three subunits (α, β, and γ). α- and β- subunits have been previously cloned in plants, but the γ-subunit has remained elusive. To isolate the γ-subunit of a plant heterotrimeric G protein an Arabidopsis thaliana yeast two-hybrid library was screened by using a tobacco G-β-subunit as the bait protein. One positive clone (AGG1) was isolated several times; it displays significant homology to the conserved domains of mammalian γ-subunits. The predicted AGG1 protein sequence contains all of the typical characteristics of mammalian γ-subunits such as small size (98 amino acids, 10.8 kDa), presence of a C-terminal CAAX box to direct isoprenyl modification, and an N-terminal α-helix region capable of forming a coiled-coil interaction with the β-subunit. Northern and Southern analyses showed that AGG1 is a single-copy gene in Arabidopsis with a similar expression pattern to the Arabidopsis β-subunit, AGB1 [Weiss, C. A., Garnaat, C. W., Mukai, K., Hu, Y. & Ma, H. (1994) Proc. Natl. Acad. Sci. USA 91, 9554–9558]. By using the yeast two-hybrid system, we show that AGG1 strongly interacts with tobacco and Arabidopsis β-subunits. The in vivo results have been confirmed by using in vitro methods to prove the interaction between AGG1 and the Arabidopsis β-subunit. As previously observed in mammalian systems, both the coiled-coil domain and the WD repeat regions of the β-subunit are essential for AGG1 interaction. Also in agreement with previous observations, the removal of the N-terminal α-helix of the AGG1 greatly reduces but does not completely block the interaction.